Tecnologia Assistiva no Brasil: impactos e desafios para a inclusão de pessoas idosas - Felipe, Eduardo Lema Cocozza (Universidade Federal de São Carlos, 2025)
This study explores the role of assistive technology (AT) in improving the quality of life and autonomy of elderly people and individuals with reduced mobility, focusing on emerging solutions and the challenges faced in Brazil. Using visualization tools such as VOSviewer and WordCloud, the research mapped key terms and their interconnections in the AT literature, highlighting themes such as artificial intelligence, robotics, and mobility aids. The findings reveal that assistive technology holds significant potential for enhancing quality of life, particularly in areas like remote health monitoring, fall prevention, and creating accessible urban environments. However, Brazil still faces considerable challenges, such as resistance from the elderly to using technology, limited access due to high costs and lack of infrastructure, and a shortage of professional training for utilizing these technologies. The study concludes that more effective public policies, alongside innovation and professional training, are essential to ensure greater accessibility and usage of assistive technology. Collaboration between the technological and social sectors will be crucial to developing solutions that meet the needs of the aging population, particularly in the context of the growing global demographic shift.
Assistive Technology in Brazil: impacts and challenges for the inclusion of older people
Keywords: Tecnologia Assistiva; Qualidade de Vida; Idosos; Mobilidade Reduzida; Inclusão Social; Assistive Technology; Life Quality; Elderly; Reduced Mobility; Social Inclusion; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::ERGONOMIA